Донские рассказы: [рассказы] - Шолохов Михаил Александрович (Поиск ; Выпуск 1 ; 1988, 1988)
Экземпляры: аб. ЦБ (20200302) / Инвентарный номер: 8601 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ш 79 / ББК: 84(2Рос=Рус)6